Animal Ethos : The Morality of Human-Animal Encounters in Experimental Lab Science - Sharp, Lesley Alexandra (Book collections on Project MUSE., 2019)
GIVEN BY JUNIATA COLLEGE IN MEMORY OF FRONIE LOUISE CERTAIN FANNING - "What are the moral challenges and consequences of animal research in academic laboratory settings? Animal Ethos considers how the inescapable needs of lab research necessitate interspecies encounters that, in turn, engender unexpected moral responses among a range of associated personnel. Whereas much has been written about codified, bioethical rules and regulations that inform proper lab behavior and decorum, Animal Ethos, as an in-depth, ethnographic project, probes the equally rich--yet poorly understood--realm of ordinary or everyday morality, where serendipitous, creative, and unorthodox thought and action evidence concerted efforts to transform animal laboratories into moral, scientific worlds. The work is grounded in efforts to integrate theory within medical anthropology (and, more particularly, on suffering and moral worth), animal studies, and science and technology studies (STS). Contrary to established scholarship that focuses exclusively on single professions (such as the researcher or technician), Animal Ethos tracks across the spectrum of the lab labor hierarchy by considering the experiences of researchers, animal technicians, and lab veterinarians. In turn, it offers comparative insights on animal activists. When taken together, this range of parties illuminates the moral complexities of experimental lab research. The affective qualities of interspecies intimacy, animal death, and species preference are of special analytical concern, as reflected in the themes of 'Intimacy, ' 'Sacrifice, ' and 'Exceptionalism' that anchor this work"--Provided by publisher.